Intercropping of upland rice with green manures in the Brazilian Cerrado - Meirelles, Flávia Constantino [UNESP]; Cavalcante, Adailza Guilherme [UNESP]; Gonzaga, Alex Rangel [UNESP]; Filla, Vinícius Augusto [UNESP]; Coelho, Anderson Prates [UNESP]; Lemos, Leandro Borges [UNESP]; Arf, Orivaldo [UNESP] (Taylor & Francis, 2022)
Cereals and green manures intercropping contributes to sustainable agriculture as it combines food production with biomass for soil cover formation. This study aimed to evaluate the intercropping of rice and green manures effects on the agronomic and qualitative performance of rice, as well as dry mass yield for the no-tillage system. A two-year experiment with 8 treatments: rice as sole crop or intercropped with Arachis pintoi, Calopogonium mucunoides, Crotalaria breviflora, Crotalaria spectabilis, Stylosanthes capitata and macrocephala, Canavalia ensiformis, and Cajanus cajan was conducted in the Brazilian Cerrado region. The results showed that the shoot dry mass and height of plants was affected by the cultivated species. Rice intercropped with A.pintoi, C.mucunoides, C.breviflora, C.spectabilis and S.capitata and macrocephala promoted yield and grain quality similar to those found with rice as sole crop. Intercropping systems of rice with C.spectabilis, C.ensiformis and C.cajan increased the number of unfilled spikelets and reduced the number of filled spikelets and yield by 33, 24 and 58%, respectively. Intercropping systems with A.pintoi, C.mucunoides, C.breviflora, C.spectabilis, C.ensiformis and C.cajan produced adequate dry mass for the maintenance of soil cover in quality no-tillage system.
Keywords: conservation agriculture; cover crops; Oryza sativaL; polyculture